2022
DOI: 10.1101/2022.10.31.514261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutamine mimicry suppresses tumor progression through asparagine metabolism in pancreatic ductal adenocarcinoma

Abstract: In pancreatic ductal adenocarcinoma (PDAC), glutamine is a critical nutrient that drives a wide array of metabolic and biosynthetic processes that support tumor growth. Despite this established dependency, the targeting of specific enzymes involved in glutamine metabolism is yet to yield any clinical benefit. Here, we have examined the therapeutic potential of 6-diazo-5-oxo-L-norleucine (DON), a glutamine antagonist that broadly inhibits glutamine metabolism. We found that DON treatment significantly blocks PD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Son et al found that genetic targeting of the gln metabolism downstream enzymes GOT1 or GOT2, resulted in a significant decrease in tumor volume in a human PDAC xenograft model, indicating these enzymes could serve as therapeutic targets (28). In accordance, Recouvreux et al reported significant decrease in tumor volume in several PDAC orthotopic models when using the pan-glutamine targeting drug, DON (32). Concerns regarding DON-related toxicity prompted the development of DRP-104, a pro-drug version (32), which showed promising responses in a syngeneic PDAC model (33).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Son et al found that genetic targeting of the gln metabolism downstream enzymes GOT1 or GOT2, resulted in a significant decrease in tumor volume in a human PDAC xenograft model, indicating these enzymes could serve as therapeutic targets (28). In accordance, Recouvreux et al reported significant decrease in tumor volume in several PDAC orthotopic models when using the pan-glutamine targeting drug, DON (32). Concerns regarding DON-related toxicity prompted the development of DRP-104, a pro-drug version (32), which showed promising responses in a syngeneic PDAC model (33).…”
Section: Discussionmentioning
confidence: 88%
“…In accordance, Recouvreux et al reported significant decrease in tumor volume in several PDAC orthotopic models when using the pan-glutamine targeting drug, DON (32). Concerns regarding DON-related toxicity prompted the development of DRP-104, a pro-drug version (32), which showed promising responses in a syngeneic PDAC model (33). Combination therapy with trametinib, a MEK inhibitor, significantly increased survival in the same model, indicating the superior potential of glutamine inhibition when combined with rationally selected complementary therapies (33).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations